Recent Labour Market Trends in the Visegrad Group Countries - Kwiatkowski, Eugeniusz (Comparative Economic Research. Central and Eastern Europe, 2011)
This study analyses labour market trends that appeared in Poland and other Visegrad Group countries during the global economic crisis, i.e. between 2007 and 2009. Special attention is paid to the changes in employment and unemployment rates that occurred in that period. For the sake of comparison, the labour market indicators are contrasted with average rates for the European Union and the euro area. The presented analysis aims to identify the degree to which unemployment rates and indicators of employment changed in the selected countries in response to the global crisis and to explain why the labour markets in the sample countries reacted differently. It also addresses the changing production volumes and labour market flexibility, particularly towards wages, employment and working time. The above analyses show that the labour markets of the Visegrad Group countries changed significantly during the global economic crisis, i.e. between 2007 and 2009; unemployment rates rose, while volumes and rates of employment decreased. In Poland, the two indicators changed their values relatively insignificantly, but in Hungary, Slovakia and the Czech Republic the changes were quite distinct. In the crisis years, Polish employment fell and unemployment increased to a relatively small degree. Although the main reason for this was the quite favourable growth trend in the Polish GDP, cuts in real wage and working time reductions also played a role. The relatively marked decline in the Hungarian employment is maliny attributed to the strong downward trend in the country’s GDP, but the decline would have probably been much more extensive, if not for the reductions in working time, real wages and labour productivity. The large declines in the Slovak and Czech employment appeared because the countries' GDPs grew smaller while real wages grew bigger. Shorter working hours and limitations on labour productivity that the two countries introduced could not reverse the unfavourable employment trends that occurred during economic downturn.